2019
DOI: 10.1039/c9se00216b
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite of nickel oxide nanoparticles and polyethylene oxide as printable hole transport layer for organic solar cells

Abstract: Low temperature NiOx is achieved using PEO as sacrificial ink additive to make hole transport layer for solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…A process has been recently reported that combines inkjet printing, low‐temperature thermal annealing at 100°C, and a short duration O 2 plasma to create NiO x electrode structures with performance characteristics that are comparable with devices that utilize conventional sol‐gel NiO x electrodes. [ 137 ] The ink consisted of NiO x nanoparticles in ethanol that were mixed with polyethylene oxide (PEO) and dispersed in diethylene glycol. The PEO aided in mitigating agglomeration of the NiO x nanoparticles.…”
Section: Schemesmentioning
confidence: 99%
“…A process has been recently reported that combines inkjet printing, low‐temperature thermal annealing at 100°C, and a short duration O 2 plasma to create NiO x electrode structures with performance characteristics that are comparable with devices that utilize conventional sol‐gel NiO x electrodes. [ 137 ] The ink consisted of NiO x nanoparticles in ethanol that were mixed with polyethylene oxide (PEO) and dispersed in diethylene glycol. The PEO aided in mitigating agglomeration of the NiO x nanoparticles.…”
Section: Schemesmentioning
confidence: 99%
“…NiO based printed devices have been used in several applications, such as pesticide detection, 36 as thermistors, 37 and as hole-transport layers in solar cells. 38 Pure ZnO is a wide bandgap semiconductor, with a direct gap of 3.37 eV, and a work function of 4.65 eV. 8,39 The presence of oxygen vacancies (V O ) causes shallow donor states near the bottom of the conduction band.…”
Section: Introductionmentioning
confidence: 99%
“…EDX surface mapping supports the confirmation of SEM analysis of Pth and Pth@NiO by indicating the presence of elemental composition. Figure 1f exhibits the presence of inorganic NiO particles in polymer matrix, in addition to C and S [36,37].…”
Section: Sem and Edx Analysesmentioning
confidence: 99%
“…Figure 1a displays the morphology of Pth matrix and, on the other hand, Figure 1b confirms the incorporation of NiO particles in Pth matrix, which is further assured by SEM micrograph of Figure 1c,d at higher magnification. EDX surface mapping supports the confirmation of SEM analysis of Pth and Pth@NiO by indicating the presence of elemental composition.Figure 1fexhibits the presence of inorganic NiO particles in polymer matrix, in addition to C and S[36,37].…”
mentioning
confidence: 99%